Methods of bathing in Roman baths (Comprehensive Journal of Science, 2026)
This research examines bathing practices in Roman baths as an integrated health, architectural, and social system that reflected an advanced level of urban organization in the Roman world. It aims to analyze the sequential stages of the bathing process, from the changing rooms through the warm and hot rooms to the cold rooms, highlighting the role of engineering techniques, particularly the hypocotaneous heating system, in achieving this precise thermal sequence.The research also discusses the health and social dimensions of bathing rituals, as baths were not merely places for personal hygiene but also spaces for social interaction, exercise, and relaxation. The study is applied to a North African city, specifically Leptis Magna, to highlight local architectural characteristics and their influence by the general Roman style.The research concludes that bathing practices in Roman baths represent an integrated system combining health functions, engineering precision, and social organization, reflecting the depth of Roman civilization and its advancement in urban planning and public services.
Keywords: bathrooms – showers – rooms – lukewarm – cold – hot – sweating